The Ukrainian War and Its Impact on the Situation of Ukrainian Refugees in Europe - Rayeq Saleem Al Brizat (RES MILITARIS, 2023)
This paper aims to investigate the impact of the Ukrainian war on the situation of the Ukrainian refugees in Europe, with the focus on the livelihood of the refugees regarding their health and psychological conditions, and how they were treated in the host countries. The researcher used the historical descriptive method to address the consequences of the Ukrainian war from different perspectives to show how the refugees were protected and treated in different European countries in terms of the services provided to them to minimize the negative impacts of the war at the social, economic, humanitarian & psychological levels. It is recommended that in order to solve this crisis, and restore peace, there is only one solutions through direct negotiations between the concerned parties to restore peace between Ukrainian and Russia since this war has caused serious implications at the global level.